What factors affect student procrastination on mathematics homework: Self-determination theory perspective - Gao, Bohao; Wijaya, Tommy Tanu; He, Yahan; Ma, Huibo; Wu, Libao (Acta psychologica, 2025)
Mathematics homework is a crucial learning activity for students, and procrastination in mathematics homework not only results in a decline in the quality of homework completion but also reduces mathematics achievement. However, there is still a lack of empirical research on what factors cause students to procrastinate on their mathematics homework. Drawing on Self-Determination Theory, this study seeks to explore factors that may be significantly associated with student procrastination in completing mathematics homework. A quantitative research design was adopted, selecting 771 middle school students from different districts of Tianjin, China as research subjects. Using Partial Least Squares Structural Equation Modeling (PLS-SEM) techniques, the study constructed structural equations to investigate the pathways through which student competence, autonomy, relatedness, and homework emotion influence mathematics homework procrastination. The research indicates that homework emotion has the greatest impact on students' mathematics homework procrastination, especially the negative emotions of anxiety and boredom, which are most evident in causing procrastination. Autonomy follows, showing a significant negative correlation with mathematics homework procrastination. Parental and teacher support for autonomy are factors of relatedness that affect students' mathematics homework procrastination. Parental and teacher autonomy support directly applied to mathematics homework often exacerbates students' procrastination in completing math assignments. This study systematically reveals the factors influencing students' mathematics homework procrastination and provides guidance for students, parents, and teachers to collaboratively reduce it in practice.